Pemulihan Kesuburan Pasca Pemakaian Alat Kontrasepsi pada Wanita Usia Subur di Indonesia - Setyaningsih, Reni Dwi; Wilopo, Siswanto Agus; Emilia, Ova (Politeknik Kesehatan Makassar, 2021)
The issue of return of fertility after discontinuation of contraceptive use is one of the important studies related to the efficacy and safety of various contraceptive methods, both hormonal and non-hormonal. Indonesian Demographic and Health Survey Data from 2002-2003 revealed that 34 percent of women in childbearing age who discontinued using the contraceptive was due to pretension to have the next pregnancy. The mechanisms of action for a variety of contraceptives would be related to the varying duration of post-use fertility return. This study was aimed to see how long it takes for women in childbearing age to stop using the contraceptive until the next pregnancy occurs. This study was an observational study using secondary data from the Indonesian Demographic and Health Survey (SDKI) data from 2002-2003. The samples of this study were 5,223 women in childbearing age who discontinued using the contraceptive. Every interest in this study was the occurrence of pregnancy after stopping using the contraceptive. Determination of the samples was limited to ever pregnant women who stopped using hormonal contraceptive and IUD, which could be observed during the survey period.The results showed that the probability of reaching 50 percent pregnancy required 7 and 6 months after the discontinuation of injection and implant use as well as 4 months after pill and IUD use. Keywords: Return of fertility, Contraceptive, Childbearing Age